Towards Paperless Education: A Preliminary Research Appliying E- Learning on Engineering Education - Lantana Dioren Rumpa; Suri Toding Lembang; Suzanna Vonny Noviana Rante; Benyamin Salu; Markus Deli Girikallo (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
Education without paper is a popular issue today. The world was hit by the global warming due to the amount of deforestation everywhere. We all know that wood is the raw material of paper. With advances in information technology today allows a learning without paper. Some technologies LMS (Learning Management System) currently allows us to conduct distance learning. Attendance in the class will not be needed anymore. Moodle is an LMS that helps teachers and students to study without having to meet physically. Google Classroom is a product developed by Google to help education through the web. In this paper we will explains the effects and benefits of google classroom. it has several advantages such as shortening the distance and time for teachers and students. It has a positive effect on the attitude and spirit of students